Comment étudier les corridors de développement ? - Nathalie Fau (EchoGéo)
At the end of the 1990s, the Asian Development Bank (ADB) promoted development corridors, also known as economic corridor. There is an important body of literature concerning corridors in Asia, written by geographer, economist and political scientist but also by international or regional organizations. This contribution confronts the operational approaches implemented by the ADB with research work conducted by scientists and academics.